STYLE VARIATION IN EARLY LANGUAGE ACQUISITION - Galián Conesa, María Dolores; Carranza Carnicero, José Antonio; Escudero Sanz, Alfonso José (Anales de Psicología / Annals of Psychology, 2006)
The aim of this work is to analyse the recent studies about individual differences in lexical development. Two questions are examined: the study about how children learn early language, and the origin of these differences. The most recent research points out temperament as relevant factor in the explication of individual differences in first language.